Serum Paraoxonase (Arylesterase) Activity in Chronic Renal Failure - Gayathri, Balasubramaniam; Usha, Anand; Vijaya, Duraisamy (Journal of Medicine, 2011)
Background: Mortality rates are higher among patients with chronic renal failure with a good proportion of this excess burden being attributable to cardiovascular disease. This excess risk is not entirely explained by elevated traditional risk factors. Among the non-traditional risk factors, serum paraoxonase (Arylesterase) activity is an important one. Materials and Methods: It was a case-control study which included total 127 subjects, 44 were non-dialysis CKD patients, 33 Heamodialysis dependent patients and 50 healthy controls. HDL-C, Apo-A and serum paraoxonase (Arylesterase) activity was estimated and compared with normal control population. Results: Serum Arylesterase activity, a measure of PON was significantly lower in CRF (on conservative management and on hemodialysis) compared to controls. Conclusion: Measurement of anti oxidant capacity of HDL-C may improve the predictive accuracy of atherosclerotic coronary artery disease, providing new strategies for the prevention and treatment of accelerated atherosclerosis in chronic renal failure. Keyword: Serum paraoxonase (Arylesterase); chronic renal failure; Atherosclerosis DOI: 10.3329/jom.v12i1.5638 J Medicine 2011; 12 : 17-20